Relationship between photosystem activity and ultraweak luminescence excitation in Cerasus humilis leaves under salt stress - Sun, Cong (Plant physiology and biochemistry : PPB, 2023)
Copyright © 2023 Elsevier Masson SAS. All rights reserved.